Impact of Perceived Parenting Styles on Social Anxiety among University Students: Mediating Role of Cognitive Styles - Abira Nadeem; Afia Misri (Research Journal of Psychology, 2025)
Purpose: The present study aimed to investigate the impact of perceived parenting styles on social anxiety, and to find out the mediating role of cognitive styles on perceived parenting styles and social anxiety. Methodology: Correlational (cross-sectional) research approach was selected to determine the effect of demographics on social anxiety in university students. Four private and four public universities in Islamabad were selected as locale from where the data was collected. The screened sample size was 536 which included 256 males and 280 females, and convenient sampling technique was used for the selection of the sample. The instruments used for the current study were General Health Questionnaire (Goldberg & Williams, 1988), The Perceived Parenting Style Scale (Divya & Manikandan, 2013), Social Phobia Inventory (SPIN, Connor et al., 2000) and Cognitive Style Indicator (Cools & Broeck, 2007). Findings: The results of the analysis showed that authoritarian and permissive parenting styles had a significant positive relationship with social anxiety; whereas, authoritative parenting style had a significant negative relationship with social anxiety. However, social anxiety was found to be non-significantly associated with cognitive styles among university students. Moreover, perceived parenting styles were found to be the significant predictor of social anxiety. Whereas, cognitive styles (knowing, planning and creating) were found to be the non-significant mediators between perceived parenting styles and social anxiety. Unique Contribution to Theory, Practice and Policy: This research has the potential to make a meaningful impact on the well-being and success of university students, which would be helpful in reducing the social anxiety among students.